ANALISIS KEMAMPUAN KOGNITIF MATEMATIS PESERTA DIDIK DITINJAU DARI GAYA BELAJAR VAK (VISUAL, AUDITORY, KINESTETIK) - Aunia Dyna Fattavi Yunianto; Aryo Andri N; Aurora Nur Aini (STKIP Subang, 2023)
This research is a descriptive qualitative research which aims to analyze cognitive abilities based on Bloom's Taxonomy which has visual, auditory and kinesthetic learning styles in class VIII A of SMP N 2 Pati. There are 6 cognitive domains, namely remembering, understanding, applying, analyzing, evaluating and creating. The subjects of this research were class 8A students consisting of 32 students and 3 students were taken, namely 1 student with a visual learning style, 1 student with an auditory learning style and 1 student with a kinesthetic learning style. This assessment data collection technique uses questionnaires, written tests and interviews. The sampling technique used is purposive sampling. The triangulation used is technical triangulation. The research results show that (1) Students with a visual learning style are able to remember, understand, apply, analyze, evaluate and create well. Students can solve questions according to the right steps and formulas so that they get good results. (2) Students with an auditory learning style are able to remember, understand, apply, analyze and create well. But students have difficulty evaluating questions. (3) Students with a kinesthetic learning style are able to remember, understand, apply and create well but have difficulty evaluating and analyzing the answers given. Therefore, it can be concluded that subjects with a visual learning style are able to fulfill all indicators of cognitive ability. subjects with an auditory learning style were able to fulfill all indicators of cognitive ability except the evaluating indicator. Subjects with a kinesthetic learning style are able to fulfill all indicators of cognitive ability except those of analyzing and evaluating.